The roles of residual martensite and plastic deformation in thermomechanically coupled functional degradation of nanocrystalline superelastic NiTi alloys - Zhao, Zhihao; Xiao, Yao; Lin, Jianping; Min, Junying (Journal of materials research and technology, 2023)
Residual martensite and plastic deformation are the culprits of functional degradation in NiTi alloys. However, their roles in thermomechanically coupled functional degradation of nanocrystalline superelastic NiTi alloys have not been investigated systematically and quantitatively. In this paper, the origins of thermomechanically coupled functional degradation of nanocrystalline superelastic NiTi alloys are subdivided into (i) plastic deformation including dislocation slipping in nanocrystals and shearing of amorphous phase, (ii) Type A residual martensite (RMA) originating from the incomplete reverse transformation during non-isothermal deformation, and (iii) Type B residual martensite (RMB) stabilized by the internal stress owing to inconsistent plastic strains among neighboring grains. For the first time, the inverse relation between fRMA and strain rate in NiTi with GS of 6 nm (a crystalline-amorphous nanocomposite) is determined experimentally. We find that the residual strain is mainly caused by plastic deformation except when RMA accumulates drastically. It is substantiated that plastic deformation lowers both forward and reverse transformation stresses significantly. Residual martensite plays an important role in the decrement of forward transformation stress, while has little impact on reverse transformation stress.